Catcalling Prevention Strategies in Handling Forms of Gender Inequality Among Students in North Sumatera - Purba, Nelvitia; Bahmid, Bahmid; Saragih, Alkausar; Batubara, Ismed; Monteiro, Seguito (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study aims to determine the legal regulations regarding catcalling, to determine the influence of student responses to catcalling and to obtain a Strategy for Preventing and Overcoming Catcalling (Sexual Harassment) in Addressing Forms of Gender Inequality for Students in North Sumatra. The analysis carried out in this study uses qualitative descriptive, namely by obtaining information related to student responses in efforts to prevent catcalling. The data analysis model used in this study is to use the deremination coefficient (R2) and the multiple linear regression equation as an indicator score using the Likert scale. The results of the study suggest that: (1). There are no legal regulations regarding catcalling yet, but there are several articles used in resolving criminal cases, including those regulated in Law Number 44 of 2008 concerning Pornography; (2). Based on the results of the calculation of the multiple linear regression equation obtained: Y = 0.229 + 0.487X1. This is indicated by the coefficient value of b1 which is positive at 0.229. Furthermore, for the independent variable X1, it shows that the value of t count = 9.147. From the t table with a significance level of α = 0.05, with the number of respondents = 20 and the number of independent variables = 1, the t table value is read = t (α, n-(k + 1)) = 1.729. Thus, for variable X 9.147> 1.729 or t count> t table which means that the independent variable X (catcalling problem) partially has a significant effect on the dependent variable Y (student perception) and (3). Strategies Implemented in the Prevention and Overcoming of Catcalling Sexual Harassment) reducing Gender Inequality is through the formation of a Law that specifically regulates Catcalling and coordination between the government, society and campus, including by forming catcalling prevention; social campaigns both through social media and slogans in society and campus.